2000
DOI: 10.1624/105812400x87879
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Pregnancy: A Perinatal Educator's Guide

Abstract: This article is a continuation in the author's growing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 4 publications
2
20
0
7
Order By: Relevance
“…Hormonal changes (increased estrogen, progesterone, and prolactin) cause nausea and breast tenderness, which together with fatigue, weakness, exhaustion and anxiety may determine difficulty of the sexual life (4,7). This reinforces the role of pregnancy as a stimulus for partners to search for new ways to enhance mutual emotional connection, intimacy and physical affi nity (8). Different studies showed that 86-100% of couples remained sexually active during pregnancy but experienced reduction in sexual activity, especially in the third trimester (1)(2)(3)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal changes (increased estrogen, progesterone, and prolactin) cause nausea and breast tenderness, which together with fatigue, weakness, exhaustion and anxiety may determine difficulty of the sexual life (4,7). This reinforces the role of pregnancy as a stimulus for partners to search for new ways to enhance mutual emotional connection, intimacy and physical affi nity (8). Different studies showed that 86-100% of couples remained sexually active during pregnancy but experienced reduction in sexual activity, especially in the third trimester (1)(2)(3)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Hecho que refleja una resistencia de los latinos en usar aparatos sexuales como recurso para la práctica sexual. De cualquier modo, su uso no es aconsejable durante la gestación, porque la gestante es más susceptible a infecciones (19).…”
Section: Discussionunclassified
“…From a clinical viewpoint, I had obtained new training in couples' intervention, adding to the training in family intervention acquired in the master's program. Postnatal sexuality Polomeno (1996aPolomeno ( ) 1996 Social support during pregnancy Polomeno (1996bPolomeno ( ) 1996 Creating family intimacy through fetal touch Polomeno (1998a), Polomeno (1999f) 1997 High-risk pregnancy Polomeno (1997bPolomeno ( ) 1997 Intimacy and pregnancy Polomeno (1997dPolomeno ( ) 1998 Health promotion for expectant fathers Polomeno (1998b), Polomeno (1998cPolomeno ( ) 1998 Labor and birth: Supporting a couple's intimacy Polomeno (1998d), Polomeno (1998e) 1999 Family health promotion from the couples' perspective Polomeno (1999e), Polomeno (1999f) 1999 Sex and breastfeeding Polomeno (1999dPolomeno ( ) 1999 Perinatal education and grandparents: Creating an interdependent family environment Polomeno (1999b), Polomeno (1999cPolomeno ( ) 1999 Sex and babies: Pregnant couples' postnatal sexual concerns Polomeno (1999aPolomeno ( ) 2000 Preparenthood and pregrandparenthood Polomeno (2000cPolomeno ( ) 2000 Sex and pregnancy Polomeno (2000b) (Polomeno, 1999b; containing fixed and curious about the transgenerationally 1999c) open questions workshop, 2) their -Conjugal intimacy was children has asked them intertwined with to come so they grandparents family intimacy (GPs) wanted to please them, -Transition to 3) needed clarity on the parenthood: 2 phases grandparental role in were involved: preconception today's context, 4) they wanted and pregnancy to e on the same wavelength -Only self-perceptions as their children in terms of the were considered latest information, 5) they (actual similarity) wanted to be a "good grandparent" -Mediators: Communication 2. The group expresses between the generations overall satisfaction with was being assessed the information given, the as well as the support that program's organization, the future and actual group dynamic approach, the grandparents can written and audiovisual provide to the materials and the comfort of the generation of the setting 3.…”
Section: The First Question: What Is a Research Program?mentioning
confidence: 99%
“…Eventually, I developed 13 workshops (Table 2) in the domain of perinatal sexuality with such themes as postnatal sexuality, intimacy during pregnancy, intimacy during labor and birth, sex and pregnancy and, sex and breastfeeding (Polomeno, 1996a;1996b;1997a;1997b;1997c;1997d;1998a;1998b;1998c;1998d;1998e;1999a;1999b;1999c;1999d;1999e;1999f;2000b;2000c). Dissemination of this experimentation was important to me so that my perinatal colleagues could also experiment with their own practice in perinatal education.…”
Section: The First Question: What Is a Research Program?mentioning
confidence: 99%
See 1 more Smart Citation